If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = p + -10 Reorder the terms: -8 = -10 + p Solving -8 = -10 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -8 + -1p = -10 + p + -1p Combine like terms: p + -1p = 0 -8 + -1p = -10 + 0 -8 + -1p = -10 Add '8' to each side of the equation. -8 + 8 + -1p = -10 + 8 Combine like terms: -8 + 8 = 0 0 + -1p = -10 + 8 -1p = -10 + 8 Combine like terms: -10 + 8 = -2 -1p = -2 Divide each side by '-1'. p = 2 Simplifying p = 2
| 0=a-18 | | 38-13=5(x-1) | | 28x-7y=-7 | | 0.5*x+0.25*x=16 | | 5x+10=28-x | | n-20=-10 | | x+22+4x=-46-4x-49 | | 8x+5=6(x+6) | | 10a-3a= | | b-1=-4 | | 6x+39=14x-23 | | 21-r=7 | | 5(x-1)+2x=7(x-3)+4 | | x-12=-41 | | 24-6x=15+3x | | 4-5y=6(3-2y) | | 8=19+x | | 3(2x-3)+11=8 | | 3x+36=8-4x | | -6=k-11 | | 5x-3=6x+9 | | 3(6-0.0033333333y)+y=18 | | 3=3a+18 | | 11x-14=107 | | 11x=97 | | 3(x+9)+129=180 | | 4(3u+5)=8u+14 | | 8(a+b)+3z=-9 | | -13+v=-28 | | 18*x=2*18+2(x) | | 4x-3-x=-18+6x | | 3(d+4)-11=321-23 |